Bone healing of dental alveoli in smokers with platelet-rich plasma obtained using single or double centrifugation. - Jonathan Harris Ricardo; María Osorio Daguer; Natalia Fortich Mesa (Universidad de Concepción., 2018)
Introduction: the habit of smoking alters the bone healing process, a problem to consider in oral surgery. Objective: To evaluate the bone healing of dental alveoli with PRP obtained using single or double centrifugation in smokers. Methodology: Extraction of mandibular third molars was performed in a study population divided into smoking group (A), which had PRP applied with the protocol using a single centrifugation step (P1C) in the alveolus of tooth 38 and the protocol of double centrifugation (P2C) in alveolus of tooth 48; a smoking group (B), to whom no PRP was applied; and a non-smokers group (C) to whom PRP was applied obtained using P1C and P2C protocol. Radiographic examination was performed at 8, 30 and 60 days post procedure. Results: Thirty patients met the criteria, 57% were female. When evaluating bone healing between the group of smokers and non-smokers, statistically significant differences were observed in the non-smoking group at 30 and 60 days, showing better results with the P2C protocol (p<0.005). Statistically significant differences were found at 30 and 60 days (p<0.005), both with the P1C and P2C when comparing bone healing of group A and B. Conclusions: Bone healing in the alveoli of mandibular third molars that which PRP applied was higher in non-smoking patients, compared with the group of smokers. Bone healing was better in patients smokers to whom PRP was applied than those without PRP treatment. Regarding the method of obtaining PRP, bone healing was better when a double centrifugation protocol (P2C) was applied.